Analysis of TikTok Utilization as a Reference Source for Students of UIN North Sumatra Library Science Study Program - Sari, Dinda Mayang; Syam, Abdi Mubarak (Journal La Edusci, 2024)
This paper examines the use of TikTok as a reference source by students in the Library Science Study Program at the University of North Sumatra with the view of determining its suitability for academic supplement. In the world where digital media and social platforms are widely used in education the concept of non-traditional sources such as TikTok is helpful. This research uses interview, observation and documentation as its data collection techniques and the data collected will be analyzed using the techniques presented by Miles and Huberman. The study shows that despite the fact that TikTok is famous for sharing informative and interesting videos, it is not well used by students as the main academic source. Some students are still skeptical, and therefore, rely on conventional learning materials, including books and scholarly journals, because of concerns relating to TikTok’s academic credibility and the risk of fake news. From the study, one can infer that social media platforms such as TikTok need to be incorporated in academic practices but in moderation while useful, they should not replace conventional sources. This research aims to add to the body of knowledge about digital literacy in higher education institutions and offers the educators an idea of how to encourage use of social media technologies and at the same time helping the students to remain active and critical evaluators of information.